Changes of solar cell parameters during damp‐heat exposure. (22nd June 2016) - Zhu, Jiang; Koehl, Michael; Hoffmann, Stephan; Berger, Karl Anton; Zamini, Shokufeh; Bennett, Ian; Gerritsen, Eric; Malbranche, Philippe; Pugliatti, Paola; Di Stefano, Agnese; Aleo, Francesco; Bertani, Dario; et al.
Abstract: The electrical ageing of photovoltaic modules during extended damp‐heat tests at different stress levels is investigated for three types of crystalline silicon photovoltaic modules with different backsheets, encapsulants and cell types. Deploying different stress levels allows determination of an equivalent stress dose function, which is a first step towards a lifetime prediction of devices. The derived humidity dose is used to characterise the degradation of power as well as that of the solar cell's equivalent circuit parameters calculated from measured current–voltage characteristics. An application of this to the samples demonstrates different modes in the degradation and thus enables better understanding of the module's underlying ageing mechanisms. The analysis of changes in the solar cell equivalent circuit parameters identified the primary contributors to the power degradation and distinguished the potential ageing mechanism for each types of module investigated in this paper. © 2016 The Authors. Progress in Photovoltaics: Research and Applications published by John Wiley & Sons Ltd. © 2016 The Authors. Progress in Photovoltaics: Research and Applications published by John Wiley & Sons Ltd. Abstract : The electrical ageing of photovoltaic modules during extended damp‐heat tests at different stress levels is investigated. Deploying different stress levels allows determination of an equivalent stress dose function, which is a first step towards the lifetime prediction of devices. The derived dose function is used to characterize the degradation of power as well as that of the solar cell's equivalent circuit parameters. This approach identifies the primary contributors to the power degradation and distinguishes the potential ageing mechanism.